Peningkatan Keterampilan Ramah Lingkungan melalui Pembuatan POC Buah Mengkudu di MTsN 1 Kota Palangka Raya - Ayu Handayani; Noor Hujjatusnaini; Rita Sukaesih (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The reading This community service activity aims to improve students' environmental skills and science literacy through training in the production and application of liquid organic fertilizer (POC) made from Morinda citrifolia fruit at MTsN 1 Kota Palangka Raya. The activity was carried out in September 2025 using an educational participatory method that actively involved MBKM UIN Palangka Raya students and students in each stage of the activity. The implementation of the activity consisted of four main stages, namely preparation, socialization, POC production practice, and evaluation and reflection. Students were trained to process noni fruit into liquid fertilizer through a fermentation process using additional ingredients of brown sugar, clean water, and EM4 solution as a microbial starter. The results of the activity showed an increase in participants' understanding of the scientific concepts of the fermentation process, organic waste management, and the application of science in everyday life. The application of POC on pakcoy plants showed better vegetative growth compared to untreated plants, characterized by greener leaves and sturdier stems. This activity not only strengthened the critical and collaborative thinking skills of the students but also fostered an environmentally conscious attitude in line with the values of the Pancasila Student Profile. Thus, the training in making POC from noni fruit can be considered a best practice in the application of contextual learning based on ecology.